A Case Study on Medicinal Plants for Swine Dermatophytosis - R. Nithiaselvi; K. Shibi Thomas; M. Dhanalakshmi; S. Maheshwari (The Indian Veterinary Journal, 2024)
The present work is a case study that was conducted at the Livestock Farm Complex, Veterinary College and Research Institute; Orathanadu (Tamil Nadu) to assess the efficacy of topical herbal plant mixtures on swine dermatophytosis. Dermatophytosis is a contagious fungal disease affecting various animal species and is a high economic burden with limited antifungal agents. Skin disease in swine can significantly impact production, carcass value and reputation; diagnosing and treating these diseases can be challenging. Eight adult sows in the farm exhibiting moist, reddish brown colour irregular foci on different parts of the body with itching were selected for the study. A mixture of three medicinal plants were selected and combined with common salt in the ratio of 5:2:2:1, comprising Acalypha indica and Azadirachta indica leaves, Curcuma longa rhizome and salt, respectively. The herbal mixture was well grounded fresh every time to make a topical paste, which was applied over the affected area three times a day for five days.  The response to the treatment was assessed based on the successful reduction of the severity of the cases. The current study’s findings suggest that the plants chosen for the study have the potential to alleviate pig’s skin disorders.